The Liver Tunnel: Intention-to-treat Validation of a New Type of Hepatectomy. Issue 2 (February 2019) - Torzilli, Guido; Procopio, Fabio; Viganò, Luca; Costa, Guido; Fontana, Andrea; Cimino, Matteo; Donadon, Matteo; Del Fabbro, Daniele
Abstract : Objective: This prospective intention-to-treat validation study evaluated the liver tunnel (LT) technique for patients having ≥1 deep centrally located liver tumor, with or without middle hepatic vein (MHV) invasion. Background: Conservative surgery has been proposed for patients with deep liver tumors having complex relationships. LT is one such novel technique. Methods: Eligible patients were prospectively enrolled for LT. LT relies on tumor-vessel detachment, and the presence of communicating veins if MHV resection is necessary. Results: Twenty consecutive patients met the inclusion criteria: 17 had colorectal liver metastases, 1 had hepatocellular carcinoma, 1 had mass-forming cholangiocarcinoma, and 1 had mixed hepatocellular carcinoma—mass-forming cholangiocarcinoma. Nineteen patients underwent LT. The MHV was resected in 6 patients, always sparing segments 4i and 5. Overall, 180 lesions were removed (median 7; range 1–37): 79 lesions were included in the LT specimen (median 3; range 1–13). There was no in-hospital 90-day mortality. Overall morbidity occurred in 10 (50%) patients: major in 2 (10%). All complications were managed conservatively. After a median 15-month follow-up (range 6–48), 2 instances of cut-edge local recurrences were observed. Conclusions: This study shows that LT is technically feasible and safe. Further studies are needed for standardizing its use. Abstract : Supplemental Digital Content is available in the text